Profile of Celestial Object Identification Skills of Junior High School Students in Indonesia (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
The ability to identify celestial objects provides significant benefits for improving students' motivation, understanding of the subject matter, reasoning, and skills, yet this area remains underexplored by researchers. This study aims to describe the profile of junior high school students' ability to identify celestial objects in science learning, particularly in the Solar System topic, focusing on their experiences in recognizing the names of celestial objects at night. Using a qualitative approach, this research involved semi-structured interviews with three science teachers and a survey of 31 7th-grade students who had not been taught the Solar System topic. The research instruments included student characteristics, availability of learning resources, challenges faced by students, teaching methods, and responses to the idea of outdoor learning with the assistance of an Augmented Reality (AR) application. The results indicate that, generally, students are not yet able to identify celestial objects other than the Moon due to limited prior experience and knowledge. Although teachers have attempted to introduce identification methods through instructional videos and direct explanations, this method is considered less accurate due to discrepancies between classroom learning and field experiences. However, both teachers and students recognize that identifying celestial objects can enrich understanding of the subject matter, increase motivation, and stimulate gratitude for God's creation. The positive response to the idea of outdoor learning with an AR application indicates high interest from both teachers and students in this approach.
Keywords: Celestial object; Solar system; Augmented Reality; Outdor learning